Extraction, quantification and characterization of oil from pumpkin seeds - Kukeera, Tonny; Banadda, Noble; Tumutegyereize, Peter; Kiggundu, Nicholas; Asuman, Ratibu (International Journal of Agricultural and Biological Engineering, 2015)
A quantification and characterization study of oil from pumpkin seeds was carried out on three pumpkin varieties, namely, Japanese type of the Curcubita maxima species, Green Kabocha and butternut squash of the Cucurbita moschanta species. Oil extraction was done using the Soxhlet method with petroleum ether as the solvent. The physicochemical properties of acid value, iodine value, specific gravity and refractive index were determined. The results were analyzed statistically using one way ANOVA at a 5% level of significance. The mean values of oil content, acid value, iodine value, specific gravity and refractive index for Japanese type pumpkin were found to be 35.67%, 2.24 mg KOH/g, 26.45 mg I2/100 g, 0.9126 and 1.47, respectively. For Green Kabocha, the mean values of the above five properties were 30.12%, 3.35 mg KOH/g, 25.3 mg I2/100 g, 0.9126 and 1.469, respectively. For the Butternut squash type the mean values of the above five properties were 34.76%, 3.74 mg KOH/g, 26.61 mg I2, 0.9131 and 1.471, respectively. It can be noted that from the low acid values of the pumpkin oil, pumpkin oil can be identified as edible. Also the low iodine value indicated that the pumpkin oil was non-drying. In addition, the low iodine value also suggested that the oil contains few unsaturated bonds and therefore has low susceptibility to oxidative rancidity. With a comparison of extraction rates from other oil sources in Uganda such as cotton (15%-20%), soybeans (19%-21%), the obtained results in this study suggested that pumpkin seeds are a viable source of vegetable oils that can be utilized for commercial vegetable oil extraction in Uganda.DOI: 10.3965/j.ijabe.20150801.013Citation: Kukeera T, Banadda N, Tumutegyereize P, Kiggundu N, Asuman R. Extraction, quantification and characterization of oil from pumpkin seeds. Int J Agric & Biol Eng, 2015; 8(1): 98－102.